Identification of β-hematin inhibitors in the MMV Malaria Box - Kim Y. Fong; Rebecca D. Sandlin; David W. Wright (International Journal for Parasitology: Drugs and Drug Resistance, 2015)
The Malaria Box, assembled by the Medicines for Malaria Venture, is a set of 400 structurally diverse, commercially available compounds with demonstrated activity against blood-stage Plasmodium falciparum. The compounds are a representative subset of the 20,000 in vitro antimalarials identified from the high-throughput screening efforts of St. Jude Children's Research Hospital (TN, USA), Novartis and GlaxoSmithKline. In addition, a small set of active compounds from commercially available libraries was added to this group, but it has not previously been published. Elucidation of the biochemical pathways on which these compounds act is a major challenge; therefore, access to these compounds has been made available free of charge to the investigator community. Here, the Malaria Box compounds were tested for activity against the formation of β-hematin, a synthetic form of the heme detoxification biomineral, hemozoin. Further, the mechanism of action of these compounds within the malaria parasite was explored. Ten of the Malaria Box compounds demonstrated significant inhibition of β-hematin formation. In this assay, dose–response data revealed IC50 values ranging from 8.7 to 22.7 μM for these hits, each of which is more potent than chloroquine (a known inhibitor of hemozoin formation). The in vitro antimalarial activity of these ten hits was confirmed in cultures of the chloroquine sensitive D6 strain of the parasite resulting in IC50 values of 135–2165 nM, followed by testing in the multidrug resistant strain, C235. Cultures of P. falciparum (D6) were then examined for their heme distribution following treatment with nine of the commercially available confirmed compounds, seven of which disrupted the hemozoin pathway.